Global, regional, and national burden of sudden infant death syndrome, 1990–2021: a comprehensive analysis of GBD 2021 data with insights into the impact during the COVID-19 pandemic - Sun, Yuhan; Peng, Haoran; Chen, Qiao; Qin, Lijie; Ren, Ying; Cheng, Yanwei (Frontiers in Pediatrics, 2025)
BackgroundSudden infant death syndrome (SIDS) remains a leading cause of infant mortality globally. Although the global burden has generally declined over recent decades, the COVID-19 pandemic may have influenced these trends. This study investigates whether the global SIDS burden has changed, particularly during the COVID-19 pandemic.MethodsData from the Global Burden of Disease (GBD) 2021 study were analyzed to estimate SIDS mortality and disability-adjusted life years (DALYs) globally, regionally, and nationally. Rates were stratified by sex, age group, socio-demographic index (SDI), and health system level. Projections were made using the Bayesian Age-Period-Cohort model and the the autoregressive integrated moving average (ARIMA) model.ResultsIn 2021, global SIDS deaths totaled 30,608, with a mortality rate of 24.16 per 100,000 infants (95% UI, 14.06–32.44). Global DALYs were 2,746,174, at a rate of 2,167.56 per 100,000 infants (95% UI, 1,261.44–2,909.59). Mortality and DALYs rates decreased by 59% from 1990 to 2021, with marked regional differences. Regions with Low SDI and Minimal health systems, particularly Sub-Saharan Africa, had the highest burden, while higher SDI and advanced health system regions reported significant declines. Male infants aged 1–5 months showed higher rates than females. Despite a global decline during the pandemic, temporary increases occurred in countries including China, the Russian Federation, and Monaco. Projections suggest continued declines, predicting a mortality rate of 16.86 per 100,000 infants and DALYs rate of 1,400.41 per 100,000 infants by 2035.ConclusionsThe global SIDS burden has consistently declined since 1990, including during COVID-19, yet significant regional disparities remain. Enhanced healthcare interventions and targeted public health initiatives are crucial, particularly in regions with Low SDI and Minimal health system resources.